(untitled) (World of finance, 2019)
Introduction. In today’s conditions of reforming local self-government and territorial organization of power, the formation of revenues of budgets of united territorial communities, as well as balancing their components, is a guarantee of the existence of financially capable, self-sufficient and developed UTC. Financially capable UTC should have sufficient resources to fulfill all their own and delegated powers. An important prerequisite for the effective functioning of UTC finances is the formation of the amount of financial resources necessary for the implementation of the functions of local self-government bodies of UTC, the timeliness and completeness of which mobilization is a determinant factor in the growth of budget revenues of territorial communities and the balancing of their structure. In the context of financial decentralization, local budget revenues are embodied in the economic independence of local self-government bodies, and their optimal structure enables them to fulfill their commitments effectively and on time. Purpose. The purpose of the article is an analysis of budget revenues of the united territorial communities, assessment of their structure, determination of factors of structural imbalances, assessment of budgetary risks in order to ensure the timeliness and completeness of the mobilization of revenues to the budgets of the joint territorial communities against the background of permanent crisis phenomena that significantly affect the economic and social development of administrative-territorial units and the state as a whole. Results. The analysis revealed a significant gap between the maximum possible and the minimum revenues to the general fund, which indicates that there is a significant disproportionate distribution of the absolute values of revenues to the general fund of the UTC budgets of the Ternopil region. It also points to the impact of structural imbalances in absolute terms on the general fund revenues of the UTC budgets of the Ternopil region. Using the regression modeling tool, the functional effect of certain types of income on the general fund revenues of the UTC of the Ternopil region was established. It has been established that general fund revenues of UTC budgets on the level of pair correlation are generally the most dependent on official transfers, domestic taxes on goods and services, local taxes, personal income tax and profit tax. Consequently, these types of revenues are structurally and systematically generating revenues of the general budget of the UTC of the Ternopil region. It is determined that the volume of revenues of the special fund of the budgets of the UTC has a fixed functional relationship only with the volume of official transfers. All other components of the revenues of the special budget of UTC budgets do not have stable relations with the revenues of this fund of community budgets, indicating a critical imbalance in its structure and increased risk. The risk of loss for the budget of UTCs is determined on the basis of the mathematical expectation of revenues to their budgets for general and special funds. In this case, the definition of the mathematical expectation of the value of the indicator by the approach of P. Chebyshev was used. Іt was established that the risk of budget revenues of UTC of the Ternopil region is determined by the budgetary risk of revenues of the general fund of community budgets. Conclusions. According to the results of the analysis, in the revenues of the general fund of UTC budgets, more system-based factors were revealed than in the special fund’s revenues. In addition, the functional dependence of the components of the general and special funds of the UTC of the Ternopil region is different in nature. This allows us to assert that the system-forming factors and factors that form functional connections form the risk of budget revenues of the UTC of the Ternopil region. Consequently, we can state that the role of general fund revenues in the budget structure of UTC of the Ternopil region is in contrast to the revenues of a special fund that does not fulfill its designated purpose in the process of financial decentralization.